ҚАРАҚАЛПАҚ ФОЛЬКЛОРЫНДА БАСҚЫ ЖАНРЫ - Баўатдинова, С. (SCIENCE and SOCIETY, 2022)
The genre of Karakalpak folklore is discussed. The genre nature of the Basque genre is analyzed. The peculiarities of the basic words of the Karakalpak people are revealed. The fact that Basky’s words are still alive among the Karakalpak people and its significance is revealed.